1991
DOI: 10.1083/jcb.114.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of sphingolipids in the endocytic pathway of HT29 cells.

Abstract: Abstract. The intracellular flow and fate of two fluorescently labeled sphingolipids, 6-[N-(7-nitro-2,1,3-benzoxadiazol-4-yl)amino]hexanoyl glucosyl sphingosine (C6-NBD-glucosylceramide) and C6-NBDsphingomyelin, was examined in the human colon adenocarcinoma cell line HT29. After their insertion into the plasma membrane at low temperature and subsequent warming of the cells to 37°C, both sphingolipid analogues were internalized by endocytosis, but their intracellular site of destination differed. After 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 14 publications
(19 reference statements)
4
46
0
Order By: Relevance
“…Similar behavior is observed for short chain lipid analogs such as C 6 -NBD-SM, which recycle efficiently upon internalization (33,34), whereas some lipid analogs containing long, saturated acyl chains (e.g. Rh-PE and some glycosphingolipids) (42,43) are targeted to late endocytic compartments.…”
Section: Altered Diic 16 Trafficking In Cholesterol-depleted or Cho-smentioning
confidence: 58%
“…Similar behavior is observed for short chain lipid analogs such as C 6 -NBD-SM, which recycle efficiently upon internalization (33,34), whereas some lipid analogs containing long, saturated acyl chains (e.g. Rh-PE and some glycosphingolipids) (42,43) are targeted to late endocytic compartments.…”
Section: Altered Diic 16 Trafficking In Cholesterol-depleted or Cho-smentioning
confidence: 58%
“…While the Golgi system is thought to be involved in the activation of ricin, several authors suggested that, at least with some cellular strains, ricin may accumulate in endosomal structures from which the A chain or the intact toxin could escape directly into the cytoplasm [20,21]; some results indicate that activation is also possible in the cytoplasm, via disulfide bond reduction [ 1 l] or proteolytic processing [22]. We searched, but did not find evidence for a differential processing of the two subunits of ricin during translocation from the plasma membrane to the Golgi (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, not all lipids follow the same processing path. Since Pagano's pioneering studies began, other researchers have used the same basic approach to study the sorting of lipids within differentiated or non-differentiated adenocarcinoma cells [34] or within polarized epithelial cells when the fluorescent lipids are introduced by spontaneous transfer to either the basolateral or apical cell surfaces [35][36][37].…”
Section: Ii-a Value As An Experimental Toolmentioning
confidence: 99%